Molecular Characterization Of E1 And E3 Maturity Loci Of Soybean [Glycine Max (L.) Merrill] Genotypes With Contrasting Maturity (Applied Biological Research, 2023)
Soybean has ten maturity loci governing its flowering time, maturity and  photoperiodism. The E1 and E3 maturity loci delay maturity and induce  photoperiod sensitivity, while their mutants are vice versa. In a field trial of 17  genotypes during kharif 2016, two early (JS 95-60 and JS 20-34) and two late  maturing genotypes (MAUS 61 and MACS 1188) were identified for further  molecular analysis. Full-length 525 bp E1 gene and partial 1688 bp E3 gene coding sequence were amplified, and sequence analysed along with reference  sequence of early maturing Harosoy. In the partial E3 gene coding sequence  studied, 26 substitution SNPs were observed, none of which was maturity  specific. In E1 coding sequences, 87 substitution SNPs were observed, of which  17 SNPs were earliness specific conserved among JS 20-34, JS 95-60 and early  Harosoy. Similarly, six amino acid frame polymorphisms were found to be  earliness specific shared amongst them. Typical B3-like conserved domains with  11 trimeric DNA binding sites were found in the E1 gene within 172-504 and  178-504 bases interval intervals in early and late varieties, respectively. Thus,  the molecular characterization of E1 maturity locus in local genotypes of  soybean can contribute for more efficient plant breeding.
Keywords: B3 conserved domain; maturity locus E1; phytochrome; soybean; SNPs